VR/AR TECHNOLOGIES FOR E-LEARNING - YUSKOVYCH-ZHUKOVSKA, VALENTINA; YASINSKIIY, ANDRIY; LOTIUK, YURII; SOLOVEІ LIUDMYLA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article is devoted to the analysis of the latest information technologies, the process of virtualization of the world educational space and the introduction of virtual and augmented reality technologies into the educational process of higher education institutions. The relationship between the real and virtual educational environment is identified and characterized. Mastery of modern information and communication technologies (ICT) is a prerequisite for a digital society. Modern students are a network generation for which the electronic way of receiving educational information is a component of their life. ICT has become their usual everyday tool, and e-learning gives them access to global educational resources and improves the quality of the educational process as a whole. In e-education, all educational content is presented only in electronic form. A feature of the development of higher education is the use of the latest advances in ICT and the emergence of a new environment - virtual, which transforms the traditional system of higher education into electronic. In many countries around the world, e-learning has become an integral part of modern education. Ukrainian higher education institutions are also moving towards e-learning as one that aims to acquire in-depth professional competencies and knowledge. Virtual reality technologies challenge researchers to increase access to the practical application of these technologies in solving professional problems. The purpose of the article is to substantiate the feasibility of using the latest digital technologies, namely virtual reality technologies in the educational process of the higher education system of Ukraine. The article uses methods of application of the latest digital technologies, namely virtual reality technologies in the educational process of the higher education system of Ukraine. The main feature of the digital space is its unique opportunities for communication, self-expression and self-determination. The Internet activity of higher education students is accompanied by a number of motives, goals, needs, attitudes, phenomena, knowledge associated with this new environment. There are many useful applications and interesting educational channels through which you can learn something new.